Legal Analysis of the Use of Electronic Evidence in Providing Evidence in Cor-ruption Cases (Decisions in Indonesia) - Saputra, Aga Naya; Aven, Ghina Salsabila (LEGAL BRIEF, 2025)
The rapid development of information technology has significantly transformed criminal procedure law, particularly regarding the recognition and use of electronic evidence. In corruption cases, electronic evidence has become a central instrument in uncovering modus operandi, tracing financial flows, and proving the involvement of perpetrators. This study aims to analyze the juridical status, practical application, and challenges of using electronic evidence in proving corruption cases in Indonesia. The research employs normative legal methods with statutory and case approaches, relying on secondary data such as legislation, legal literature, and relevant court decisions. The findings indicate that electronic evidence has obtained normative legitimacy through the Electronic Information and Transactions Law, the Anti-Corruption Law, and progressive judicial decisions. In practice, electronic evidence plays a decisive role in major corruption cases, although its implementation faces challenges related to authenticity, integrity, limited technical capacity of law enforcement officers, and regulatory disharmony. In conclusion, electronic evidence strengthens the evidentiary system in corruption cases, but legal harmonization, forensic technical standards, and capacity-building for law enforcement are required to ensure effectiveness and legal certainty.